Postoperative pain treatment after lumbar discectomy. A protocol for a systematic review with meta‐analysis and trial sequential analysis. Issue 2 (8th December 2021) - Zachodnik, Josephine; Bech‐Azeddine, Rachid; Udby, Peter M.; Sandberg, Magnus; Thybo, Kasper H.; Geisler, Anja
Abstract: Background: Patients undergoing lumbar discectomy usually suffer from moderate to severe pain during the postoperative period. Multimodal, or balanced analgesia, is the leading treatment principle for managing postoperative pain. The rationale is to achieve optimal pain treatment through additive or synergistic effects of several non‐opioid analgesics, and thereby, reducing the need for postoperative opioids, facilitating early mobilization and functional rehabilitation. For discectomy surgery, evidence of both the benefit and harm of different analgesic interventions is unclear. Objectives: This systematic review aims to investigate the benefits and harms of analgesic interventions in adult patients after lumbar discectomy. Methods: This protocol for a systematic review is written according to The Preferred Reporting Items for Systematic Review and Meta‐Analysis Protocols guidelines. We will search The Cochrane Library's CENTRAL, PubMed, EMBASE, and ClinicalTrails.gov for published and ongoing trials. All randomized clinical trials assessing the postoperative analgesics effect of an intervention with a control or no‐intervention group undergoing lumbar discectomy will be included. Two authors will independently screen trials for inclusion using Covidence, extract data and assess the risk of bias using Cochrane's risk‐of‐bias 2 tool. We will analyse the data using Review Manager and Trial Sequential Analysis. Meta‐analysis will be performed according to the Cochrane guidelines. We will present our primary findings in a 'summary of findings' table and evaluate the overall certainty of evidence using the GRADE approach. Discussion: This systematic review will assess the benefits and harms of analgesic interventions after lumbar discectomy and have the potential to improve best practices and advance research.